Smithsonian horizons. - Adams, Robert McC. (Smithsonian)
Comments on how corporate and institutional users of computer technology must anticipate and plan for an awesome increase in the volume of intercommunication and in the part it plays in the daily conduct of business. Increases in bandwidth for communications channels; View of John A. Armstrong, IBM's Vice President of Science and Technology; How the ever deepening network of communication will be significant for the Smithsonian; More.